Analisis Kesiapan Guru terhadap Perkembangan Teknologi dalam Pembelajaran Geografi di SMAPAB 8 Saentis - Alvian Maranalom Siregar; Kiki Renhardi Napitupulu; Lusia Oktaviani; Queen Helen Br. Bukit; Rosma Purba; Qamara Aulia; Elfayetti Elfayetti (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This research is based on the demands of the Independent Curriculum which emphasizes the importance of utilizing technology, such as Geographic Information Systems (GIS), digital mapping applications, and interactive learning platforms, to improve the quality of learning. However, the results of observations show that the use of technology by teachers is still not optimal, even though schools already have basic facilities such as projectors and computer laboratories. In this study, the data collection technique uses primary data. The primary data design carried out for this study in data collection was carried out through observation, interviews and questionnaires. Interviews were conducted with geography teachers at SMA PAB 8 Saentis to obtain data on readiness in using learning technology. This study identified several factors that influence teacher readiness, including limited facilities, lack of experience and mastery of technology, and student readiness in accessing technology. In addition, the main obstacles faced include limited facilities, uneven student access, and lack of training for teachers. This study emphasizes the importance of supporting facilities, ongoing training, and increasing digital literacy for teachers and students so that the integration of technology in geography learning can run effectively and optimally.